2010
DOI: 10.1080/02699930903223766
|View full text |Cite
|
Sign up to set email alerts
|

Negative affective environments improve complex solving performance

Abstract: Based on recent affectÁcognition theories (Bless et al., 1996;Fiedler, 2001;Sinclair, 1988), the present study predicted and showed a differentiated influence of nice and nasty environments on complex problem solving (CPS). Environments were constructed by manipulating the target value ''capital'' of a complex scenario: Participants in the nice environment (N042) easily raised the capital and received positive feedback, whereas those in the nasty environment (N042) hardly enhanced the capital and got negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 16 publications
0
32
0
2
Order By: Relevance
“…[2][3][4][5][6][7], the dimensions of the problem are slightly smaller, but are within the same order of magnitude (e.g. 15 (9) vs. 11 (7) control variables (integer) and 16 vs. 12 state variables per month).…”
Section: The Iwr Tailorshop-modelmentioning
confidence: 98%
See 2 more Smart Citations
“…[2][3][4][5][6][7], the dimensions of the problem are slightly smaller, but are within the same order of magnitude (e.g. 15 (9) vs. 11 (7) control variables (integer) and 16 vs. 12 state variables per month).…”
Section: The Iwr Tailorshop-modelmentioning
confidence: 98%
“…However, solving (1) to proven global optimality is already a challenging task. The novel methodological approach has also been combined with experimental studies [6,7,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conflicts are essential to enhance collaborative skills, therefore conflict situations are vital to collaborative problem solving performance (Mitchell and Nicholas 2006;Scardamalia 2002;Stahl 2006;Weinberger and Fischer 2006). It includes handling disagreements, obstacles to goals, and potential negative emotions (Barth and Funke 2010;Dillenbourg 1999). For example, the tendency to avoid disagreements can often lead collaborative groups towards a rapid consensus (Rimor et al 2010), while students accept the opinions of their group members because it is a way to quickly advance with the task.…”
Section: Discussionmentioning
confidence: 99%
“…Positive moods at a medium level of activation were found to facilitate adequate, planned, and reflective problem-solving behaviours in a study by Reither and Stäudel (1985), whereas negative emotions increased the tendency to avoid a problem by shifting attention to easier tasks (Schwarz and Bless 1991). However, Spering et al (2005) and Barth and Funke (2010) showed that negative feedback from the problem environment triggered negative affect which in turn might enhance problem solving. Still, from a perspective of emotion regulation (Gross 1998), it is important to regulate these negative emotions even if they represent valuable feedback on the progress of problem solving (Hannula 2015).…”
Section: Domain-specific Problem-solving Competencementioning
confidence: 99%